Effective treatment with daratumumab in post-HSCT refractory immune-mediated cytopenias: a case report and literature review - Jing, Xiao-yu; Li, Dong-jun; Su, Sheng-nan; Dai, Qing-kai; Sun, Shu-wen; Huang, Liang; Ai, Yuan; Gao, Ju; Zhu, Yi-Ping; Ni, Jia-qi; Lu, Xiao-xi (Frontiers in Immunology, 2025)
Immune-mediated cytopenias (IMCs) following allogeneic hematopoietic stem cell transplantation (HSCT) can lead to substantial morbidity and mortality, presenting a major therapeutic obstacle. Here, we report a case of a pediatric patient with acquired aplastic anemia. Nine months after HSCT, this patient developed severe, refractory hemolytic anemia and immune-mediated thrombocytopenia (IMT). Despite treatment with corticosteroids, intravenous immunoglobulin (IVIG), rituximab, along with avatrombopag, romiplostim, acetylcysteine, and decitabine, the patient’s platelet count showed no signs of improvement. Subsequently, daratumumab, a monoclonal antibody targeting CD38, was administered. This treatment induced a rapid and sustained response. Four months after initial daratumumab administration, the percentage of CD38-positive immune cells in the patient’s peripheral blood increased, which was concurrent with another decline in platelet levels. After re-initiating daratumumab therapy, the patient’s platelet count returned to normal levels. The only significant adverse effect noted was a delayed recovery of humoral immunity. Daratumumab, by targeting antibody-producing plasma cells, shows promise as a therapeutic alternative for refractory IMCs in post-HSCT patients.